Some evidences of recent and holocenic evolution of the cryosphere in Friuli Venezia Giulia (Italy) - Colucci, Renato (Università degli studi di Trieste, 2013)
2011/2012 The cryosphere, an integrated part of the Earth system, refers to that portion of the physical world that exists in its frozen state. Ice caps, sea ice, icebergs, lake ice, snow cover, ground ice, glaciers and ice sheets and shelves obviously belong to this set. It also comprises all those parts of territory which, though not presenting water in solid state, always maintain temperatures below zero (i.e. permafrost environments). Studies on the cryosphere of Friuli Venezia Giulia were almost always referred to the attempt of reconstructing the major glacial phasesof the Pleistocene period. The only studied aspect of today’s cryosphere is that of the small glaciers of the Julian Alps, on which terminus shrinkage or advances measurements were taken since the end of the 19th century. The fact that today’s cryosphere isn’t studied that much is probably due to its scarcity compared to other sectors of the Alps. This work intends to fill this gap, trying to characterise as best as possible the present state of the cryosphere on the Friuli Venezia Giulia territory. In order to do so the whole mountain territory of Friuli Venezia Giulia was taken into consideration, ultimately focusing on two distinct sectors: the Julian Alps (south-east area), which hosts the last glacial remains on the Canin and Montasiomassifs, and the Carnic sector of the Alps (north-west area). The latter is the only one that was involved in a survey aiming at the characterisation of mountain permafrost, due to investigations made to realise the rock glaciers inventory of the Italian Alps. A third aspect, still not deeply analysed also on a global level though potentially capable of bringing crucial developments in the future, is that of permanent ice deposits inside cavities. The so named IceCaves are just one of several peculiar phenomena which show a reaction to climate and somewhat sparse research over the past few decades has shown that ice in temperate caves holds similar and complementary secrets to ice elsewhere. Friuli Venezia ...